The precocious pregnancy experience in the perception of the adolescents from the community of Manga - Terezinha Ferreira; Maria Irismar de Almeida; Lia Carneiro Silveira (Rev Rene)
Our practice in attending adolescents of a periphery community in the state of Ceará has shown a considerable incidence of pregnancy in this age group. Starting from these observations we developed this study with the objective of learning about the adolescent’s perception concerning the determinative factors and repercussions of their pregnancy. The data which was found show that the adolescents studied are in the majority of low income levels and with little knowledge concerning sexuality. Their feelings concerning pregnancy vary from acceptance to rejection. We conclude through this study that the actions directed towards this age group are still incipient and we suggest forms of developing them.